Drug addiction and substance use disorders - Horning, Nicole (Diseases and disorders series., 2020)
Concise explanations offer an overview of substance abuse disorders, what causes them, how people live with them, and the latest information about treatment and prevention. Includes primary and secondary source quotations, annotated bibliographies, and lists of organizations to contact for additional information.